FITC-labeled d-glucose analog is suitable as a probe for detecting insulin-dependent glucose uptake. Issue 22 (1st December 2018) - Su, Lin; Wu, Rui; Chen, Xinrou; Hou, Wei; Ruan, Benfang Helen
Graphical abstract: Abstract: The detection of the insulin-dependent glucose uptake is a vital part in the research of diabetes. To establish a sensitive assay for measuring glucose uptake in living cells, we synthesized a FITC linkedd -glucosamine2 as a probe.2 was obtained by the reaction of commercially availabled -glucosamine hydrochloride and FITC and was determined as a single anomeric form by 1 H NMR and 13 C NMR.2 exhibited good water solubility and stability. An uptake assay in HepG2 cells with or without insulin demonstrated that FITC showed strong cellular uptake, whereas uptake of2 is much less but is insulin dependent. This suggests that2 is specifically transported into cells through a receptor that is regulated by insulin and has potential application in screening of compounds or genes that regulate the insulin-dependence in cell-based assays.